The Role of Product Development Costs in Moderate Managerial Ownership Seen From The Indicators of Return on Asset, Cash Ratio, and Total Asset Turnover - Devi Putri Ananda; Denny Kurnia; Deni Sunaryo (International Journal of Economics, Management and Accounting, 2024)
This research aims to determine the effect of Return on Assets, Cash Ratio, Total Assets Turnover to Managerial Ownership with Product Development Costs as a Moderating Variable. This research uses the Pharmaceutical subsector company objects on the Indonesia and Malaysia Stock Exchanges for the 2013-2021 period. The data collected is secondary data with a documentation method in the form of the company's annual report. The analytical tool used to test the hypothesis is IBM SPSS V21. The sampling method used in this research used a purposive sampling technique to obtain 10 companies that presented complete financial reports, resulting in 90 samples. The analysis technique used is descriptive statistical analysis, classical assumption test, moderated regression analysis (MRA), multiple linear regression, t test, and f test. The research results partially concluded that Return on Assets and Cash Ratio influences managerial ownership while Total Assets Turnover has no effect on Managerial Ownership. The results of the research simultaneously show a calculated f value of 3.099 and an f table of 2.71, meaning calculated f > f table or a significance value of 0.031 <0.05. So Return on Assets, Cash Ratio, and Total Assets Turnover has a simultaneous effect on Managerial Ownership. Research results Moderated Regression Analysis (MRA) shows that Product Development Costs can moderate the Return relationship on Assets to Managerial Ownership and Product Development Costs can moderate the Cash relationship Ratio to Managerial Ownership. Meanwhile, Product Development Costs cannot moderate the Total Asset relationship Turnover on Managerial Ownership. For further research, it is hoped that it will examine other sub-sectors and add other variables.